Comparative efficacy of various CHIs combined with western medicine for non-small cell lung cancer: A bayesian network meta-analysis of randomized controlled trials - Peng, Ciyan; Chen, Jing; Cui, Wei; Li, Sini; Li, Jianhe; Peng, Liubao (Frontiers in Pharmacology, 2022)
Background: Given the limitations of Western medicine (WM) for the treatment of non-small cell lung cancer (NSCLC) and the wide exploration of Chinese herbal injections (CHIs), systematic evaluation of the efficacy and safety of different CHIs for treatment of NSCLC is imperative. In this study, we performed a network meta-analysis to evaluate the comparative efficacy and safety of 16 CHIs combined with WM regimens for the treatment of NSCLC. Methods: Literature databases were searched from their inception to November 2021, and all randomized control trials (RCTs) involving NSCLC patients treated with a combination of Chinese and WM were retrieved. Outcomes, including disease control rate, survival quality score, incidence of gastrointestinal adverse reactions, incidence of leukopenia, and incidence of thrombocytopenia, were analyzed using RevMan (5.3), Stata17, and R software. Surface under the cumulative ranking curve (SUCRA) probability values were calculated to rank the treatments examined, and clustering analysis was used to compare the effects of CHIs on different outcomes. Results: A total of 389 studies involving 31,263 patients and 16 CHIs were included.The results of the network meta-analysis showed that, with WM treatment as a co-intervention, CSI was most likely to improve the disease control rate (SUCRA = 80.90%), HQI had the highest probability of being the best option for improving the survival quality score (SUCRA = 82.60%), DCI had the highest probability of reducing the incidence of gastrointestinal adverse reactions (SUCRA = 85.50%), HCSI had the highest probability of reducing the incidence of thrombocytopenia (SUCRA = 91.30%), while SMI had the highest probability of reducing the incidence of leukopenia (SUCRA = 79.10%). Conclusions: CHIs in combination with WM are more effective and safer than WM alone and may be beneficial for patients with NSCLC. SMI+WM and DCI+WM are most likely the optimal CHI to improve disease control rates, survival quality score, and reduce adverse effects. This study has limitations; therefore, higher quality RCTs and real-world evidence are required to support our conclusions.